Glitching Intuitions: Speculative Fiction as an Affective Realism of the Present. - Dadacz, Katy (Contemporary Literature)
In the article, the author discusses how speculative fiction can depict affective realism in present time by analyzing William Gibson's book "Pattern Recognition," which deals with the uncertain present and a pervasive crisis of futurity. Also cited are other works like "The Visitors" by Jessi Jezewska Stevens and "Oval" by Elvia Wilk, the dialectic of realism and speculation and the affective and cognitive relations between algorithmic machines and humans.